2023
DOI: 10.3389/fcimb.2023.1157918
|View full text |Cite
|
Sign up to set email alerts
|

Gut dysbiosis in autoimmune diseases: Association with mortality

Abstract: To better understand the impact of gut dysbiosis on four autoimmune diseases [Sjögren’s syndrome (SS), systemic lupus erythematosus (SLE), rheumatoid arthritis (RA), and multiple sclerosis (MS)], this review investigated the altered gut bacteria in each disease and the shared ones among the four diseases. The enriched gut bacteria shared by three of the four autoimmune diseases were Streptococcus, Prevotella, and Eggerthella, which are associated with autoantibody production or activation of Th17 cells in immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 108 publications
0
3
1
Order By: Relevance
“…Decreased abundance of Defluviitaleaceae and Peptococcaceae were reported in patients with autoimmune diseases such as systemic lupus erythematosus 34 , rheumatoid arthritis 35 , juvenile idiopathic arthritis 36 , and Graves' disease 25 , while how they participate in the pathological process of MG remains unclear and requires further investigation. Surprisingly, our study identified genus Faecalibacterium, also a member of Firmicutes, as a risk factor for MG, though it was found to be depleted in patients with systemic lupus erythematosus, multiple sclerosis, and Sjögren's syndrome in previous findings 37 . Evidence has suggested that Faecalibacterium could produce several metabolites such as pentanoate and butyrate in the intestine, leading to Treg cell activation and various anti-inflammatory activities with protective benefits 38,39 .…”
Section: Discussioncontrasting
confidence: 68%
“…Decreased abundance of Defluviitaleaceae and Peptococcaceae were reported in patients with autoimmune diseases such as systemic lupus erythematosus 34 , rheumatoid arthritis 35 , juvenile idiopathic arthritis 36 , and Graves' disease 25 , while how they participate in the pathological process of MG remains unclear and requires further investigation. Surprisingly, our study identified genus Faecalibacterium, also a member of Firmicutes, as a risk factor for MG, though it was found to be depleted in patients with systemic lupus erythematosus, multiple sclerosis, and Sjögren's syndrome in previous findings 37 . Evidence has suggested that Faecalibacterium could produce several metabolites such as pentanoate and butyrate in the intestine, leading to Treg cell activation and various anti-inflammatory activities with protective benefits 38,39 .…”
Section: Discussioncontrasting
confidence: 68%
“…Although there is a lack of research about the association between Eggerthella and FM, increased abundance of Eggerthella has been reported in various disorders, such as depression ( Barandouzi et al, 2020 ; Liu et al, 2022 ), rheumatoid arthritis ( Chen et al, 2021a ), schizophrenia ( Karpiński et al, 2023 ), systemic lupus erythematosus ( He et al, 2016 ), and multiple sclerosis ( Chang and Choi, 2023 ), all of which are common comorbidities of FM. Eggerthella can increase intestinal permeability and promote the production of pro-inflammatory cytokines ( Salem et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the genera Eggerthella and Sutterella were related to increased WBC and GlycA levels after multiple-testing correction, respectively. It was reported that both genera Eggerthella (Chang and Choi, 2023) and Sutterella (Hiippala et al, 2016;Kaakoush, 2020) have pro-inflammatory properties. An increasing number of studies have shown that Eggerthella lenta could be an important pathogen for humans, even causing life-threatening infection under certain conditions (Jiang et al, 2021b), which can drive Th17 activation in immune-related diseases (Alexander et al, 2022).…”
Section: Discussionmentioning
confidence: 99%